The effects of polaronic mass and conduction band non-parabolicity on a donor binding energy under the simultaneous effect of pressure and temperature basing on the numerical FEM in a spherical quantum dot. (April 2017) - Sali, A.; Kharbach, J.; Rezzouk, A.; Ouazzani Jamil, M.
Abstract: Basing on the numerical Finite Element Method (FEM), we have investigated the influences of polaronic mass and conduction band non-parabolicity on the binding energy of the ground state of an on-center hydrogenic donor impurity in a spherical G a A s / G a 1 − x A l x A s quantum dot structure. The calculations have been made with a realistic potential barrier height in the framework of the effective mass approximation including the combined effect of hydrostatic pressure and temperature. The donor binding energy is computed as a function of dot size, Al concentration x, hydrostatic pressure and temperature both in the absence and presence of polaronic mass and conduction band non-parabolicity effects. We have taken into account the electronic effective mass, dielectric constant, and conduction band offset between the dot and barriers varying with pressure and temperature. It has been found that the binding energy is strongly affected by the effect of polaronic mass and conduction band non-parabolicity for narrow quantum dot and large Al concentration x. The results show again that the donor binding energy increases linearly with the pressure in direct gap regime and its variation is larger for narrower dots only and drops slightly with the temperature. A good agreement is obtained with the existing literature values. Highlights: The donor binding energy increases linearly with the pressure in direct gap regime. The donor binding energy decreases as the temperature increases. The non-parabolicity effects enhances the donor binding energy for narrow dots. The non-parabolicity effect is more prominent than the polaronic mass for small dot radii.